2023
DOI: 10.1007/s00381-023-06117-6
|View full text |Cite
|
Sign up to set email alerts
|

How often do awake craniotomies in children and adolescents lead to panic and worry?

K. Daniel O’Leary,
Anastasia J. Philippopoulos,
Alexis Koslofsky
et al.

Abstract: Purpose Awake craniotomy (AC) is the treatment of choice for the resection of brain tumors within eloquent brain regions for adults, but not much is known about its psychological impact on children and adolescents. Patient immaturity and difficulty in cooperating during surgery could result in psychological sequelae postoperatively, such as anxiety, panic, and worry. Methods In this review, we examined eight studies assessing AC performed on patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The importance of patient motivation and family cooperation for awake surgery in pediatric patients has been reported [ 12 ]. A review by O’Leary et al [ 13 ] also reported that although awake surgery in children and adolescents is generally performed without problems, some patients may show postoperative panic disorder, highlighting the importance of preoperative and postoperative psychological assessments. Although the patient in the present study was 15 years old, his understanding of the disease and motivation were very high, and he underwent awake surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of patient motivation and family cooperation for awake surgery in pediatric patients has been reported [ 12 ]. A review by O’Leary et al [ 13 ] also reported that although awake surgery in children and adolescents is generally performed without problems, some patients may show postoperative panic disorder, highlighting the importance of preoperative and postoperative psychological assessments. Although the patient in the present study was 15 years old, his understanding of the disease and motivation were very high, and he underwent awake surgery.…”
Section: Discussionmentioning
confidence: 99%